Bone marrow and kidney fat as indicators of condition in reindeer - Nieminen, Mauri; Laitinen, Matti (Rangifer, 1986)
Back-fat depth, kidney-fat index (KFI), fat and triglyceride contents in femur and metatarsal marrows were measured from 92 semi-domesticated reindeer (Rangifer tarandus tarandus L.) in northern Finland during 1980-84. The age of the reindeer varied from 5 months to 10 years and marrow fat content was estimated by five different methods: standard ether extraction, oven-drying (Neiland, 1970), reagent-dry assay (Verme and Holland, 1973), compression method (Greer, 1968) and visual estimation (Cheatum, 1949). The kidney-fat index (Riney, 1955) was significantly related (r=0.892) to the percent marrow fat in femur and metatarsus. The oven-drying method gave high correlations with results obtained by ether extraction and reagent-dry methods. Oven-drying produced a lower mean dry-weight value than reagent-drying (1.31 ±0.36%). The amount of compression had a concave relationship with the ether-extractable fat content of femur and metatarsal marrows. The subjectiveness of the visual estimation technique limited its use. Femur marrow fat contents (dry-weight %) in reindeer which died from starvation varied between 2 - 8%. Metatarsal fat contents were slightly higher. Adult males had a mean triglyceride content of 46.8 |Jmol/g in August in the femur. Adult females had slightly lower values. The amount of triglycerides was significantly related to the ether-extractable fat content of the femur (r=0.914) and metatarsal (r=0.911).